Analisis sosial ekonomi masyarakat terhadap pemanfaatan taman lindung hutan mangrove di Desa Sidodadi Kec. Teluk Pandan Kab. Pesawaran Lampung - Ahmad Ersan; Anista Rahmawati; Dania Hellin Amrina (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2022)
Mangrove forests hold important benefits for the environment and socio-economic community living around mangrove forest protected park areas. The existence of a mangrove forest protected park in the area is an added value to the area, in addition to being a tourist spot for the community, the existence of this mangrove forest can also reduce abrasion on the coast. And also with the existence of this mangrove forest, it can be one of the incomes of the surrounding community. However, it does not solve poverty because of inappropriate income. In this mangrove area, there are not only professional fishermen from the surrounding community, but some are gardening and farming as well as trading, some even work in offices and civil servants. The mangrove forest protected park was established around 2016/2017 which was funded by PT Japfa and of course assistance from the government. With the existence of this mangrove forest protected park area, it is hoped that it will become an example for the community about the importance of protecting the environment and surrounding sustainability, thereby minimizing the indiscriminate felling of trees which can actually become a natural disaster for the community around the area.